Perancangan Interior Studio Program Studi Desain Interior Gedung P2 Universitas Kristen Petra di Surabaya - Christian Sutedjo; Hedy Constancia Indrani (Intra, 2014)
Studio design is one of the useful facilities to plan a design product. Interior Design of Christian University has a great potency to change the present studio to become better studio which has better quality to develop the design learning process and comfort of the students in studio. In order to use that great potency, “Ultimate Studio” concept is apllied. Within this concept, the ideas of multi functional furniture design and interior element appear to help the student activities and to give comfortable atmosphere in the studio so that the teaching and learning process in the stuio can be condusive and optimal. The facilities in the studio designed need to be adapted with the students needs by dividing the studio to be areas which can help the students activites and give better atmosphere in the studio. This plan is expected to reach optimal result to bring positive functional effect for the design studio of Petra Christian University